PENGARUH DANA BAGI HASIL DAN PENDAPATAN ASLI DAERAH TERHADAP ASET TETAP INFRASTRUKTUR DENGAN BELANJA MODAL SEBAGAI PEMEDIASI - Muharrami, Widia; Ikhsan, Adhisyahfitri Evalina; Fadhlia, Wida; Aidafitri, Fauziah (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2024)
This study aims to examine the effect of revenue-sharing funds (DBH) and local original income (PAD) on infrastructure fixed assets (ATI), with capital expenditure as a mediating variable, in provincial governments in Indonesia. The population of this study includes all provinces in Indonesia, totaling 34 provinces. The sample was selected using a purposive sampling technique, with 138 provinces chosen as the sample. The data used in this study is secondary data in the form of Local Government Financial Reports from 2018 to 2022, which have been audited by the Audit Board of the Republic of Indonesia (BPK-RI). The data analysis method is multiple linear regression with a path analysis approach. The hypothesis testing results show that revenue-sharing funds (DBH) and local original income (PAD) have a positive and significant effect on capital expenditure. Revenue-sharing funds (DBH) and local original income (PAD) also have a positive and significant impact on infrastructure fixed assets (ATI). Revenue-sharing funds (DBH) and local original income (PAD) affect infrastructure fixed assets (ATI), which are partially mediated by capital expenditure.